Community intellectual disability nurses' public health roles in the United Kingdom: An exploratory documentary analysis. (March 2018) - Mafuba, Kay; Gates, Bob; Cozens, Maria
The aim of this study was to explore how public health policy in the United Kingdom was reflected in community intellectual disability nurses' (CIDNs)' job descriptions and person's specifications. The role of CIDNs has evolved due to policy changes. As these roles evolve, job descriptions and person specifications are important in highlighting employer's expectations staff, priorities, and professional values of their employees. This study involved an exploratory documentary analysis of n = 203 CIDNs' job descriptions and person specifications in the context of role theory. The CIDNs' public health roles identified in this study are health education, health protection, health prevention, health surveillance, and health promotion. Key policies themes were intellectual disability health access, public health strategies, policy evaluation/redesign, and public health policy. There is a lack of public health role clarity and inconsistency in role expectations across organizational boundaries in the United Kingdom.